Shotgun sequencing of sonication fluid for the diagnosis of orthopaedic implant-associated infections with Cutibacterium acnes as suspected causative agent - Ponraj, Diana Salomi; Lund, Michael; Lange, Jeppe; Poehlein, Anja; Himmelbach, Axel; Falstie-Jensen, Thomas; Jørgensen, Nis Pedersen; Ravn, Christen; Brüggemann, Holger (Frontiers in Cellular and Infection Microbiology, 2023)
Orthopaedic implant-associated infections (OIAI) due to Cutibacterium acnes (C. acnes) can be difficult to diagnose. The aim of this pilot study was to determine if metagenomic NGS (mNGS) can provide additional information to improve the diagnosis of C. acnes OIAI. mNGS was performed on sonication fluid (SF) specimens derived from 24 implants. These were divided into three groups, based on culture results: group 1, culture-negative (n=4); group II, culture-positive for C. acnes (n=10) and group III, culture-positive for other bacteria (n=10). In group I, sequence reads from C. acnes were detected in only one SF sample, originating from a suspected case of OIAI which was SF and tissue culture-negative. In group II,C. acnes sequences were detected in 7/10 samples. In group III, C. acnes sequence reads were found in 5/10 samples, in addition to sequence reads that matched the bacterial species identified by culture. These samples could represent polymicrobial infections that were missed by culture. Taken together, mNGS was able to detect C. acnes DNA in more samples compared to culture and could be used to identify cases of suspected C. acnes OIAI, in particular regarding possible polymicrobial infections, where growth of C. acnes might be compromised due to a fast-growing bacterial species. However, since SF specimens are usually low biomass samples, mNGS is prone to DNA contamination, possibly introduced during DNA extraction or sequencing procedures. Thus, it is advisable to set a sequence read count threshold, taking into account project- and NGS-specific criteria.